Structural biopolymer preservation in Miocene leaf fossils from the Clarkia site, northern Idaho. - Logan, G A (1993)
The 17- to 20-million-year-old locality at Clarkia, northern Idaho, is renowned for yielding amplifiable DNA from a magnolia leaf fossil. In-source pyrolysis-mass spectrometry and pyrolysis-gas chromatography/mass spectrometry now reveal that molecular preservation of biomacromolecules is highly selective; structural polysaccharides, cutin polyesters, and proteins were not preserved in detectable quantity in the leaf tissues, whereas both lignin and an aliphatic biopolymer were detected. This study points up the need for improved understanding of the precise modes and extent of preservation of biomacromolecules in fossil materials and sediments.